Creative life-orientation, creativity and giftedness in hierarchy and comparison [Креативность, творчество и одаренность в иерархии и сравнении] (in Russian) - Иванченко, Андреянна Алексеевна; Ivanchenko, Andreyanna; Іванченко, Андреянна Олексіївна (Миколаїв: МДУ ім. В.О. Сухомлинського, 2011)
In this paper for the first time we propose to distinguish the conceptual and terminological definitions of creativity, creation and giftedness phenomena. Creativity is considered as a dynamic process of coming-to-be and maintenance of much-enveloping salutary individual state. The positive-genetic influence of creative life-orientation on the psycho-somatic-physiological state of health and general individual life-organization are shown. В статье впервые предлагается разграничить понятийно-терминологические определения феноменов «креативность», «творчество» и «одаренность». Креативность рассматривается как динамический процесс становления и поддержания многообъемлющего благотворного личностного состояния. Показано позитивогенное влияние креативности на психо-сомофизиологическое самочувствие и общую жизнеорганизацию личности.
Keywords: смешение; самочувствие; психическое состояние; благотворный; динамический; динамический; этимология; творчество; креативность; подменивать